2022
DOI: 10.3390/diagnostics12092249
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Concentration of Survivin and Caspase 3 in Habitual Tobacco Chewers with and without Oral Squamous Cell Carcinoma in South Indian Rural Population—A Case Control Study

Abstract: Background: There is paucity of data on tissue levels of Survivin and Caspase 3 in south Indian tobacco chewers with oral Squamous cell carcinoma (OSCC). Oral cancer is a rapidly growing, highly prevalent head and neck malignancy; it involves a mucosal epithelium of a buccal cavity exposed to tobacco and other carcinogens. The basis of the survival of a tumor cell or transformed normal cell into a neoplastic cell is by the suppression of apoptosis regulation. Recently, researchers have focused on Survivin, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the current study we found a higher concentration of survivin and higher nuclear staining in tobacco chewers with OSCC compared to control samples. The finding in the study indicated tobacco as a contributing factor to increasing survivin concentration, and its predominant nuclear staining of survivin can be considered as a predictor factor for the malignant progression of the cells in habitual tobacco chewers with OSCC [39].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the current study we found a higher concentration of survivin and higher nuclear staining in tobacco chewers with OSCC compared to control samples. The finding in the study indicated tobacco as a contributing factor to increasing survivin concentration, and its predominant nuclear staining of survivin can be considered as a predictor factor for the malignant progression of the cells in habitual tobacco chewers with OSCC [39].…”
Section: Discussionmentioning
confidence: 74%
“…The research findings suggested that survivin may serve as a biomarker in cancerous conditions. Our earlier research mentioned the quantitative estimation of tissue survivin and caspase 3 among the population addicted to tobacco chewing, in tobacco chewers with oral cancer [39].…”
Section: Introductionmentioning
confidence: 99%